Jordanian survivors' experiences of recovery from critical illness: a qualitative study. (10th November 2014) - Abdalrahim, M.S.; Zeilani, R.S.
Abstract : Background: Despite the fact that a lot of patients consider their discharge from hospitals as a positive sign of progress towards regained health, many of them start suffering from physical, psychological and social problems after discharge from intensive care units. Aim: This study aims to describe the experiences of Jordanian survivors of critical illnesses 3 months after discharge from a hospital intensive care unit. Methods: A descriptive qualitative approach was used to involve 18 Jordanian patients from two hospitals in a major Jordanian city using open‐ended interviews. Interview transcripts were analysed using content analysis method. Results: Three main themes have emerged from the data: (1) new meaning of life; (2) different perspectives on the meaning of life, and (3) struggle for role identity. Limitation: The sample was chosen from one city in Jordan; longitudinal study might help identify the change in patients' experiences over time. Conclusion: Patients described the discharge from the intensive care unit as a means of rescue from death; they began to value their spiritual and religious rituals. Negative traumatic experiences hindered the patients' recovery process. During recovery, patients struggled to resume their power and role in family. Implications for Nurses and Health Policy: This study emphasizes the importance of providing care according to the patient's individual needs, related to their cultural and spiritual milieu; there is a need to develop follow‐up services for ICU survivors within a national health policy. Further educational and training programmes in the patient's issues after discharge from hospital are needed. This will definitely help nurses care after this patient group.